Prospects and problems of working students in selected food establishment in Iloilo City - Burao, Jurida C.; Cantery, Mary Joy; Fernandez, Ruby; Jancinal, Arlene; Rocero, Rosalyn
Sixty working students in selected food establishment in Iloilo were given questionnaires by the researchers. Random sampling was employed and descriptive analysis was used. In the level of analysis simple statistical tools as frequency distribution and percentages were availed. Findings revealed that most of the working studnets are 20 years of age, single, and eldewst or second in the family. They are in the fourth and third year in college ; in enrolled in business-related courses enrolled in the University of the Philippines in the Visayas ; not availing any scholarship grant ; performing satisfactorily in school ; currently enrolled this semester ; and enrolled with 18 units. They have fathers who are laborers ; have mothers who are housekeepers ; belong to a family of 6 members ; belong to a family with an average annual income of P 0 - 45,000 ; belong to a family with at least one member who is also enrolled in college ; and receive a weekly allowance of P201-300 from their parents. These working students work as service crew ; required to work at 100 hours a month ; cited time constraints as their primary difficulty ; work because they want to gain experience, personal development and earn money for themselves.